LOCAL CONVERGENCE FOR JARRATT-LIKE ITERATIVE METHODS IN BANACH SPACE UNDER WEAK CONDITIONS - Argyros, I. K.; George, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
We study the method considered in Sharma and Arora(2014), for solving systems of nonlinear equations, modified suitably to include the nonlinear equations in Banach spaces. Our conditions are weaker than the conditions used in earlier studies. Numerical examples where earlier results cannot apply to solve equations but our results can apply are also given in this study.